VD_FINDINFO Pron / 2014 / 19 vom 14. Februar 2014 - VD Tribunal cantonal (2014)
TRANSACTIONACCORD, ASSISTANCE JUDICIAIRE, INDEMNITÉEN GÉNÉRAL, FRAIS JUDICIAIRES, DÉPENS | 241 al. 1 CPC (CH), 241 al. 2 CPC (CH)